Lipid transfer protein syndrome in a Northern European patient: An unusual case report - Albert, E.; Walsemann, T.; Behrends, J.; Jappe, U. (Frontiers in Medicine, 2023)
Non-specific lipid transfer proteins (nsLTPs) as the primary sensitizer in plant-food allergic patients used to be seen primarily in the Mediterranean area. However, more recently, increasing numbers of clinically relevant sensitizations are being observed in Northern Europe. We herein report an unusual case of a woman who developed an anaphylactic reaction during a meal including a variety of different foods ranging from fruits and nuts to oats, wheat, and salmon. Allergy diagnostics showed no Bet v 1 sensitization but an nsLTP-mediated food allergy. Despite the much more prominent birch food syndrome in Central and Northern Europe, LTPs should be considered disease-causing agents, especially for patients developing severe reactions after consuming LTP-containing foods.